The Relationship Between Permissive Parenting Styles and Students’ Aggressive Behavior at SMA Negeri 2 Medan - Asiah; Rohimi Sebayang (Era Scientific Publisher, 2025)
This study aimed to examine the relationship between permissive parenting styles and students’ aggressive behavior at SMA Negeri 2 Medan. A quantitative approach with a correlational research design was employed. The sample consisted of 70 eleventh-grade students selected using purposive sampling based on school counselors’ records regarding aggressive behavior and parental parenting style characteristics. The research instruments included a permissive parenting questionnaire and an aggressive behavior questionnaire, each developed based on established theoretical indicators. The results of hypothesis testing revealed a positive and statistically significant relationship between permissive parenting and students’ aggressive behavior, with a correlation coefficient of 0.435 and a significance value of 0.000 (p < 0.05). This finding indicates that higher levels of permissive parenting are associated with a greater tendency for students to exhibit aggressive behavior. The study recommends increased attention and targeted interventions by school counselors to identify and address students who come from permissive parenting backgrounds.